The main trends in the digital economy and finance that shape the current landscape and vector of development of industries - Xu, Wang; Kievich, A.V. (Экономика и банки, 2024)
The article analyzes and substantiates the fact that nowadays, and it can be stated with certainty, the world volume of digitized information is growing exponentially. And the size of these data sets is so large that traditional programs for their processing can no longer cope with them. Let us rightly ask ourselves the question: can we (humanity) cope with such a volume of digitized information (Big Data)? Thus, according to IBS calculations, in 2013 only 1.5% of accumulated data sets had information value. And by 2025, according to forecasts, humanity will have already generated more than 100 zettabytes of information. Fortunately for us, the world will be saved by Big Data processing technologies. They will allow people to embrace the immensity and benefit from it. And this gives unprecedented opportunities to optimize all spheres of our life: public administration, medicine, telecommunications, economy and finance, transport, production, it improves the efficiency and competitiveness of companies around the world, etc. Here we especially emphasize that in the field of digital finance, the prospects for Big Data development are even more promising. Thus, with the emergence of new technologies and the growth of data volume, new areas of special interest are also emerging, namely: the provision of financial services thanks to the revolutionary movement known as Open Banking, digital wallets and contactless payments, blockchain technology and cryptocurrencies, robo-advisors (advisors) and financial services based on artificial intelligence, embedded finance, etc. And this really provides unprecedented opportunities to optimize and manage all areas of our life.